A study on Device for Child Safety and Tracking - Lohiya, Chanksha (Journal of Advanced Research in Signal Processing and Applications, 2021)
Child   safety   and   is a significant worry as the greater number of violations on kids a re detailed these days. With this inspiration, a reasonable IoT gadget for kid security and following is created to help the oldsters to find and screen their youngsters. The framework is created utilizing Link It ONE board modified in inserted C and interfaced with temperature, heartbeat, contact sensors and GPS, GSM and camera modules. The oddity of the work is that the framework an automatically    alerts the parent/caretaker by sending SMS when quick consideration is needed for the youngster during crisis. The parameters like touch, temperature &heartbeat of the child are utilized for parametric examination and results are plotted for a same. The above framework guarantees the security and following of adolescents. How to cite this article: Lohiya C, Chauhan N, Singh Y. A Study on Device for Child Safety and Tracking. J Adv Res Sig Proc Appl 2020; 2(2): 5-7.